(untitled) (Swiss Medical Weekly, 2023)
Oral anticoagulants (antivitamin K, direct oral anticoagulants) are routinely prescribed for the prevention or treatment of thromboembolic events, and many patients are now on long-term anticoagulant therapy. However, this complicates the management of urgent surgical conditions or major bleeding. Various strategies have been developed to reverse the anticoagulant effect and this narrative review provides an overview of the wide range of therapies currently available.